Exploring the impact of English song listening habits on listening proficiency - Widyaningtyas, Yulisa; Pratolo, Bambang Widi (ASSOCIATION FOR SCIENTIFIC COMPUTING ELECTRICAL AND ENGINEERING (ASCEE), 2024)
This study examines the correlation between the listening proficiency of third-semester English Education students at a private university in Indonesia and their habits of listening to English songs. Data collection involved a questionnaire designed to gauge students' frequency and genre preferences in listening to English music alongside Mid-Term Examination (UTS) scores used to indicate their listening proficiency. A Lilliefors normality test was conducted on the data related to students' listening skills and their song-listening habits, yielding significant values of 0.020 and 0.200, respectively. The null hypothesis (H0), which assumes that the data follows a normal distribution, was considered in this context. The Spearman’s rho correlation test, a non-parametric measure for determining the direction and strength of the association between two variables, revealed a correlation coefficient of -0.125 between students' listening proficiency and their English song-listening habits. The negative coefficient suggests a weak negative correlation between these variables. However, careful interpretation of this coefficient, including its associated two-tailed p-value, is necessary to determine the statistical significance of the observed relationship. The weak negative correlation observed indicates that listening to English songs as a habit may not substantially enhance listening proficiency in academic contexts. This finding suggests that while exposure to English music may offer informal language exposure, it may not directly translate into improved academic listening skills. Consequently, educators and curriculum developers should consider supplementing informal listening practices with structured listening exercises specifically tailored to students' linguistic and comprehension needs. This study underscores the need for a more comprehensive approach to developing listening skills within English language education.